(untitled) (Legal journal - Research in Legal and Social Sciences, 2023)
This paper studies the existing limits between life in gestation -fetus- and independent life -in the sense of another living human being-, in order to determine the moment in which the fetus becomes another, for the purpose of the correct application of the norm in Paraguayan criminal law. En este trabajo se realiza un estudio de los límites existentes entre la vida creciente −feto− y la vida independiente −en el sentido de otro ser humano vivo−, con el objeto de determinar el momento en que el feto se convierte en otro, a los efectos de la correcta aplicación de la norma en el derecho penal paraguayo. In this sense, the Penal Code makes a clear distinction between the other -material object of homicide, intentional or negligent- and the fetus -material object of abortion-, but does not define the concept of other. The research is of the documentary type, with a qualitative approach and non-experimental design. The methods of interpretation of the law were used, a hermeneutic study was carried out with a bibliographic review of the exponents, who take a position regarding the moment when the fetus becomes another, in order to elaborate a category of analysis. An example was given from a case study and it was concluded that the boundaries between life in gestation and independent life can be determined, i.e. when the fetus becomes another.